The Argument of "a priori" in the Logic of Functioning of "Empirical" Concepts - Комаха, Л. Г. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
In the paper a problem of "a priori" as an argument in justifying philosophy of "conceptual pragmatism" by K. Lewis. The analysis of the logic disposition functioning of meanings (a priori concepts), forming a new experience and a new thinking.